Worldview in Gothic Story by E. F. Benson “Gavon’s Eve” - M. A. Burtseva (Научный диалог)
The issues of creating a picture of the world in the story of the English writer E. F. Benson’s “Gavon’s Eve”. It is concluded that the picture of the world is organized by two external chronotopes: the chronotope of the Scottish village of Gavon, the chronotope of the Pictish fortress and the internal chronotope, concentrated around the consciousness of the narrator. Attention is paid to the functioning of forms of artistic space and time, built on the principle of binary oppositions. It is shown that spatial correlations between external and internal, far and near, western and eastern have an increased semantic significance in the narrative. Particular attention is paid to the role of the spatial categories of up and down, revealing the author’s concept of the eternity of infernal evil. It has been proven that the key forms of artistic time are day and night, light and dark, past and present, which are traditional for Gothic subjects. The relevance of the study is due to the growing interest in the genre of gothic prose, which today is associated, in particular, with attempts to resist anti-humanistic, destructive trends in the life of modern society. The novelty of the research is seen in the fact that the issues of artistry    of Gothic stories by E. F. Benson is still underresearched.